If $(\vec a×\vec b)×\vec c=\vec a×(\vec b×\vec c)$, where $\vec a,\vec b$ and $\vec c$ are any three vectors such that $\vec a.\vec b ≠0, \vec b.\vec c ≠0$, then $\vec a$ and $\vec c$ are |
inclined at angle of $\frac{π}{3}$ between them inclined at angle of $\frac{π}{6}$ between them perpendicular parallel |
parallel |
We have, $(\vec a×\vec b)×\vec c=\vec a×(\vec b×\vec c)$ $⇔-\{\vec c×(\vec a×\vec b)\}=\vec a×(\vec b×\vec c)$ $⇔-\{(\vec c.\vec b)\vec a-(\vec c.\vec a)\vec b\}=(\vec a.\vec c)\vec b-(\vec a.\vec b)\vec c$ $⇔-(\vec c.\vec b)\vec a+(\vec a.\vec c)\vec b=(\vec a.\vec c)\vec c-(\vec a.\vec b)\vec c$ $⇔-(\vec c.\vec b)\vec a=-(\vec a.\vec b)\vec c$ $⇔(\vec c.\vec b)\vec a=(\vec a.\vec b)\vec c$ $⇔\vec a=\frac{(\vec a.\vec b)}{(\vec c.\vec b)}\vec c$ $⇔\vec a=λ\vec c$, wherer $λ=\frac{\vec a.\vec b}{\vec c.\vec b}$ $⇔\vec a$ and $\vec c$ are parallel. |